SEXIST LANGUAGE IN THE SPEECH ACTS OF THE CHARACTERS IN THE MOVIE ON THE BASIS OF SEX (2018) - Muhamad Fathi Rizqi; Sari Rejeki; Ni Made Widisanti (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study aims to show the types, functions, and forms of speech acts, types of sexist language, and the perlocutionary effect of sexist language in the speech of the characters in the movie On the Basis of Sex. This study uses qualitative method and observation and note-taking technique. Based on the results of the analysis, the type of speech act found are representative, directive, expressive, and commissive types. Perlocutionary speech acts reveals non-verbal, non-verbal verbal, and verbal types. The characters’ speech proves the presence of sexist language such as hostile sexism, protective paternalism, competitive gender differentiation, heterosexual hostility, complementary gender differentiation and dominative paternalism. The speech also caused negative effects on female characters such inability to fight back, feeling helpless, decreased self-confidence, and anger.